Soft Computing Techniques for Reduced Order Modelling: Review and Application. Issue 1 (2nd January 2016) - Alsmadi, Othman; Abo-Hammour, Zaer; Abu-Al-Nadi, Dia; Saraireh, Saleh
Abstract: As the mathematical procedure of system modelling often leads to a comprehensive description, which causes significant difficulty in both analysis and control synthesis, it is necessary to find lower order models, which maintain the dominant characteristics of the original system. In this paper, different soft computing (named as artificial intelligence (AI)) techniques are presented, applied, and analysed for model order reduction (MOR) of multi time scale systems with the objective of substructure preservation. In addition to that, we investigate the firefly optimization technique for MOR with substructure preservation. The analysis is concerned with the optimization approach and quality of method performance.